2020
DOI: 10.2139/ssrn.3572881
|View full text |Cite
|
Sign up to set email alerts
|

Sex-Bias in COVID-19: A Meta-Analysis and Review of Sex Differences in Disease and Immunity

Abstract: A striking anecdotal feature of the Coronavirus disease 2019 (COVID-19) outbreak is the difference in morbidity and mortality between the sexes. Here, we present a meta-analysis of 206, 128 reported cases to demonstrate that whilst there is no difference in the proportion of males and females with confirmed COVID-19, male patients have more than double the odds of requiring intensive treatment unit admission (OR 2.5) and higher odds of death (OR 1.60) when compared to females. We review data revealing how prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Gender differences were found in both infection and hospitalization rates, indicating that male ASD participants had higher rates of both infections and hospitalizations. This finding is consistent with previous literature (Peckham et al, 2020;Vahidy et al, 2021) which generally demonstrated higher COVID-19 hospitalization and infection rates in male subjects. It has been suggested that sex differences in the immune system explain the differences between the sexes in COVID-19.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Gender differences were found in both infection and hospitalization rates, indicating that male ASD participants had higher rates of both infections and hospitalizations. This finding is consistent with previous literature (Peckham et al, 2020;Vahidy et al, 2021) which generally demonstrated higher COVID-19 hospitalization and infection rates in male subjects. It has been suggested that sex differences in the immune system explain the differences between the sexes in COVID-19.…”
Section: Discussionsupporting
confidence: 93%
“…It has been suggested that sex differences in the immune system explain the differences between the sexes in COVID-19. Studies reporting of gender differences in COVID-19 infection and hospitalization rates suggest that female immune system has a more robust response to COVID-19 because of a more prominent production of INFalpha compared to males (Peckham et al, 2020). Thus, it is possible that male ASD participants are more immunologically vulnerable to COVID-19, while female ASD patients share the same robust immunological response.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has also been shown to increase the expression of ACE2 [86]. There has been evidence suggesting that a potential cause for the differential presentation of COVID-19 between males and females (higher odds of ICU admissions and death in males) is due to different expressions of ACE2, which results in a heightened and more effective immune response in females [87][88][89]. The influence of ACE2 expression on COVID-19 severity is determined at this stage, where it has been established that ACE2 is expressed in greater concentrations in males than females [90,91].…”
Section: Overviewmentioning
confidence: 99%
“…A comparison of all available gender-divided data of COVID-19 cases lead to the conclusion that males are not more likely to get infected but have higher severity and fatality rate. 8,9 Comparing these results with similar diseases, for example SARS-CoV1 by using data from China and infecting mice, there is a higher mortality rate of males, especially in older age groups in SARS-CoV1 3,10 , a virus similar to SARS-CoV2. Studies which tried to examine the cause of the biased behaviour of COVID-19 towards gender have largely found that the two enzymes ACE2 6 and TMPRSS2 can be seen as connected to the gender bias of COVID-19.…”
Section: Introductionmentioning
confidence: 91%